Incorporating Oral Health Considerations for Medication Management in Care Transitions - Kimberly A. Sanders; Christine L. Downey; Anita Yang; Brooke K. Baker (MDPI AG, 2020)
Transitions of care involve multifaceted considerations for patients, which can pose significant challenges if factors like oral health are overlooked when evaluating medication management. This article examines how oral health factors should be considered in medication management of patients who may be at risk for hospital readmission. This article also explores successes and challenges of a pharmacy consult service integrated into a dental clinic practice, and the opportunities within that setting to improve overall patient outcomes including those related to care transitions.